Characterization and parametric study of mesoporous calcium titanate catalyst for transesterification of waste cooking oil into biodiesel. (1st December 2016) - Yahya, Noor Yahida; Ngadi, Norzita; Jusoh, Mazura; Halim, Noor Amirah Abdul
Highlights: Simple synthesis of mesoporous calcium titanate by sol-gel-hydrothermal method. Improvement of characteristics and catalytic activity from commercial CaO. Production of biodiesel at relatively mild reaction conditions. Abstract: Mesoporous calcium titanate (MCT) catalyst was synthesized via a sol-gel-hydrothermal method and investigated as a catalyst for biodiesel production from waste cooking oil (WCO). Calcium was supported on titanate in order to increase their surface area, stability and consequently, improve its performance in the transesterification of WCO to biodiesel. Synthesized catalyst was characterized with powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), N2 physisorption, Fourier transform-infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA) and carbon dioxide temperature-programmed desorption (CO2 -TPD). The catalyst possessed high surface area, basicity and stability than calcium oxide (CaO) catalyst. The highest biodiesel yield achieved was 80.0% in 3:1 of methanol to WCO molar ratio, 0.2 wt.% of MCT catalyst for 1 h at 65 °C. Reusability study suggested that this catalyst can be recycled for five successive runs.